Cytotoxicity Produced by Silicate Nanoplatelets: Study of Cell Death Mechanisms - Huang, Jie-Ting; Chang, Ling-Chu; Cheng, Chung-Ssu; Lin, Jiang-Jen; Huang, San-Yuan; Chen, Shuen-Ei (Toxins, 2020)
Nano-silicate platelets (NSP), an exfoliated product from natural clays, have been validated for biosafety and as an effective supplement to alleviate mycotoxicosis. Since NSP induced noticeable cell death, we therefore investigated further the mechanism of cytotoxicity caused by NSP. Exposure to NSP impaired membrane integrity and caused cell death in a dose-dependent manner. Reactive oxygen species (ROS) generation other than of NADH oxidase origin, and subcellular interactions by internalized NSP also contributed to NSP-induced cell death. NSP persistently provoked receptor-interacting protein 1 Ser/Thr (RIP1) kinase and caspase 6 and 3/7 activation without altering caspase 8 activity and induced evident chromatolysis of necrosis in the later stage. These events proceeded along with increased ER stress and mitochondrial permeability, to final Cyt-C (Cytochrome C) release and AIF (apoptosis inducing factor) translocation, a hallmark of cell necroptosis. Fluorescent probing further manifested NSP traffic, mostly adherence on the cell surfaces, or via internalization, being compartmentalized in the nuclei, cytosols, and mitochondria. Pharmacological approaches with specific inhibitors suggested that endocytosis and particularly RIP1 kinase provocation mediate NSP-induced cell death independent of caspase activation. In conclusion, the necroptotic process contributes to most of the cell death induced by NSP due to membrane interactions/impaired integrity, ROS generation, and subcellular interactions by internalized NSP.